Advances in magnetic resonance. - Waugh, John S. (John Stewart) (Academic Press, 1977)
Advances in Magnetic Resonance, Volume 9 describes the magnetic resonance in split constants and dipolar relaxation. This book discusses the temperature-dependent splitting constants in the ESR spectra of organic free radicals; temperature-dependent splittings in ion pairs; and magnetic resonance induced by electrons. The electron impact excitation of atoms and molecules; intramolecular dipolar relaxation in multi-spin systems; and dipolar cross-correlation problem are also elaborated. This text likewise covers the NMR studies of molecules oriented in thermotropic liquid crystals and diffusion.